The Ambivalent Image of Some Women's Arts in Selected Literary Works : A Comparative Study - Hadeel Abdel-Fattah Mohammed Eslam; Shereen Abouelnaga (2024)
Oriental dance is one of the most controversial forms of art. Despite its popularity within Egyptian society, Oriental dance is regarded as a symbol of shame and immorality. On the other hand, in orientalist narratives, a dancer of Raqs Sharqi represents the exoticness and sexual promise of the Orient. In line with the outburst of the sex revolution in the 1960s, many white feminists attempted to redefine and develop the image of oriental dance. Despite the popularity of such empowerment movements, many of the oriental dance performers, especially those that belong to working-class Cairo, undergo intersectional discrimination. This study delves into the factors governing the portrayal of oriental dance in different literary and cinematic works; namely Naguib Mahfouz s Palace Walk, George William Curtis Nile Notes of A Howadji, and At Night They Dance by Isabelle Lavigne, Stéphane Thibault.
. . . . . . : .
Thesis (M.A.)-Cairo University, 2024.
Bibliography: pages 105-116.
Issued also as CD
Text in English and abstract in Arabic & English.
Keywords: Dance; Oriental Dance -- Comparative Literature -- Cultural Studies -- Social Realism